The Effect of Balanced Nutrition Feeding Time on Improving the Nutritional Status of Stunting Children - Sari, Ria Setia; Ratnasari, Febi; Susilowati, Yuni (Future Science, 2021)
Stunting is a nutritional problem that has a negative impact on achieving optimal growth and development in children. One of the causes of stunting is the inaccuracy of giving balanced nutritional food. The purpose of this study was to analyze the timing of giving balanced nutritional foods to the nutritional status of stunting children, using a quasi-experimental method, one group pre, and post-test design. The sample of this research was taken by accidental sampling technique as many as 45 respondents. The analysis test used Wilcoxon with the result of Sig 0.000 (< 0.05), where there was an effect of the time of giving balanced nutrition to the nutritional status of stunting children in the work area of ??the Tangerang District Health Office.